Phenomenon of the Increasing Single Candidates and Backsliding Democratic Values in Indonesia - Febrian Febrian; Iza Rumesten; Nurhidayatuloh Nurhidayatuloh; Neisa Angrum Adisti (Hasanuddin Law Review, 2022)
One interesting thing to discuss regarding the holding of regional head elections in 2020 is the increasing number of single candidates participating in democracy contestation. This article offers a comprehensive assessment of the theoretical and practical connections between the number of single candidates in holding regional head elections to the weakening of democratic values in regional head elections. The research methodology adopted for this research was normative. The results show that the factors causing the increase in the number of single candidates are the high threshold that must be met by political parties, an expensive political dowry, and the failure of political parties in carrying out the regeneration function. The increasing number of single candidates in regional head elections is synonymous with the decline in democratic values because the closure of the freedom space for the people to choose candidates. A single pair of candidates will close the freedom space for the people to elect their candidate for leader. A single pair of candidates in regional head elections can close the freedom space for the people to know and discuss the vision, mission, and work program of the single candidate pair. A single candidate in the regional head election is a violation of human rights because it has the potential to block the opportunity for the lower middle class to compete in the elections. The regional head elections with a single candidate will limit broader community participation.